pH-responsive gum tragacanth hydrogels for high methylene blue adsorption - Illanes, Cristian Omar (2023)
Background: Biobased hydrogels are used in many applications due to their easy availability, low cost, and versatility to acquire different structures. However, there is scarce information about the changes generated in the matrix's microstructure after crosslinking reactions. The effect of the crosslinking reaction using glutaraldehyde on the micro- and macrostructure of tragacanth gum hydrogels (TG GLU) was evaluated. Results: New acetal groups, which increase with increasing glutaraldehyde (GLU), produced less packed biopolymeric structures with more thermal stability. Due to demethoxylation, a higher amount of free carboxylic groups after crosslinking reaction were determined in TG GLU. Crosslinked hydrogels presented a higher water uptake capacity with a pH-responsive behavior with suitable thermal and mechanical properties. Besides this, the highest adsorptive capacity of methylene blue achieved was qm = 530 mg/g. Conclusions: pH responsive gels from tragacanth were obtained after crosslinking with glutaraldehyde. Chemical and microstructural changes affected the methylene blue adsorption, resulting in hydrogels with improved adsorptive properties. These properties give the TG-GLU hydrogels some features that make them suitable for practical applications in the pharmaceutical industry related to drug delivery and water remediation. © 2023 Society of Chemical Industry.